The Killing of a Bull Muskox by a Single Wolf - Gray, David R. (ARCTIC, 1970)
Gives a detailed description of a 53-min contest between a male Canis lupus and a 5-6 yr old bull Ovibos moschatus wardi on Bathurst Island, 28 May 1968. The wolf's maneuvers succeeded in exhausting the muskox. The wolf returned to feed on the carcass for four days succeeding the kill, at least three more times during the summer and, accompanied by a female, fed on it briefly six times in June-Aug 1969.